Stress, epileptiform symptoms in schizophrenia and neural information transmission - Simek Jakub; Bob Petr; Pec Ondrej; Chladek Jan; Hajny Jakub; Raboch Jiri (Translational Neuroscience)
Several findings indicate that stress may influence epileptiform discharges manifesting in temporal-limbic areas, which may become a potential trigger of psychosis that may manifest without neurologically diagnosed epilepsy. Some findings suggest that measures assessing levels of inter-hemispheric information connection may reveal the spread of subclinical epileptiform neural activity associated with psychotic and seizure-like symptoms. Recent research also suggests that electrodermal activity (EDA), which is related to limbic activations, may allow indirect measurement of interhemispheric information transmission. These findings about the interhemispheric spread of information suggest a hypothesis that heightened spread of information between the brain hemispheres might indirectly indicate epileptiform discharges spreading between hemispheres.